Mascot Design as Brand Identity Communication Science Study Program UMSIDA - Febrillian, Kevin Wahyu; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Mascots serve as effective visual identity elements for various organizations to convey character uniquely. Specific background: The Communication Science Study Program at Universitas Muhammadiyah Sidoarjo (UMSIDA) uses